'Just another Saturday night'. (7th October 2012) - Cheyne, I; Anderson, L
Abstract : Background: Hawkes Bay (East Coast NZ) is made up of 4 districts within the region including, two medium sized cities and two rural communities. Hawkes Bay features significantly in statistics involving youth and alcohol serious and fatal crashes. 'Just Another Saturday Night' is a resource featuring a local crash. Two youth where killed and two critically injured. The purpose of the digital video disc is to demonstrate the full impact of a crash on the victims and associated individuals. Aims/Objective/Purpose: Overall aim is to reduce incidence, severity of youth and alcohol crashes and demonstrate the broader impacts on passengers, families, rescue services and the community as a whole. Raise awareness drivers are responsible for all road users' safety. Change the attitude of young drivers around driving impaired and increasing passenger safety. Provide unique educational opportunities in varying venues and present these involving Jared, survivor of the crash to further reduce risk, harm. Methods: Conducted over 2000 surveys prior to the presentation to identify the audience understanding of consequences of driving impaired, we then undertook 2000 post surveys. These highlighted a change in attitude in 92% of the participants. Results/Outcome: There has been a reduction in accepted claims involving motor vehicle crashes on public roads. An example is provided for: Hastings District 2009/10: 674-2010/11: 586 Napier City 2009/10: 530-2010/11: 472. Significance/Contribution to the Field: With the success of the resource we have launched this nationally and continue to have outstanding feedback from educators across New Zealand